Perceived organizational support and job satisfaction: The does knowledge sharing mediate it? - Zulkifli Musannip Efendi Siregar; Muhammad Arfan Harahap; Reni Novianti Sari; Sri Karyani Damanik (Nur Science Institute, 2026)
This study aims to determine the effect of perceived organizational support on job satisfaction, with knowledge sharing as a mediating variable. The research method used is quantitative research. The sample for this study comprised 211 teachers from Labuhanbatu Regency, South Labuhanbatu Regency, and North Labuhanbatu Regency. Data were analyzed using SmartPLS software with the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results showed that perceived organizational support influenced teacher job satisfaction. This means that increasing perceived organizational support is very important to increasing teacher job satisfaction. Perceived organizational support has a positive and significant effect on knowledge sharing, and knowledge sharing has a positive and insignificant effect on teacher job satisfaction. The results showed that knowledge sharing did not significantly mediate the relationship between perceived organizational support and job satisfaction. The findings imply that policymakers and school administrators should strengthen teacher support through recognition, well-being initiatives, fair career development, open communication, and adequate work facilities.